EFEKTIFITAS LKPD BERBASIS PENDIDIKAN KARAKTER MENGGUNAKAN MODEL GUIDED DISCOVERY PADA MATERI GARIS DAN SUDUT DI KELAS VII SMP NEGERI 2 KOTA BENGKULU - Veliesa, Gyzka; Hanifah, Hanifah; Maulidiya, Della (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2021)
This study aimed to produce the Development of Student Worksheets Based On Character Education Using Guided Discovery Model on Line and Corner Material In Class VII SMPN 2 Bengkulu that is valid category. This research was a research development (Research and Devolopment) by modifying 4D Thiagarajan procedure into 3 phases namely define, design, and development phase consisting of effectiveness test. Effectiveness LKPD was tested on thirty three students in class VII G SMP Negeri 2 Kota Bengkulu even semester of academic year 2017/2018. This research instruments effectiveness sheet. The results showed that: The Development of Student Worksheets Based On Character Education Using Guided Discovery Model on Line and Corner Material In Class VII SMPN 2 Bengkulu City included in category effective on the basis of: 1) the response of learners consisting of 11 items of statement with average score 47.10 in very good category; 2) the activities of learners consisting of 11 items statement with an average score of 46.25 in very good category; 3) educator activity consisting of 10 items statement with average score 43,13 in very good category; and 4) learning outcomes of learners achieve classical mastery 84.85%.